A comprehensive review of the applications of bacteriophage-derived endolysins for foodborne bacterial pathogens and food safety: recent advances, challenges, and future perspective - Khan, Fazal Mehmood; Chen, Jie-Hua; Zhang, Rui; Liu, Bin (Frontiers in Microbiology, 2023)
Foodborne diseases are caused by food contaminated by pathogenic bacteria such as Escherichia coli, Salmonella, Staphylococcus aureus, Listeria monocytogenes, Campylobacter, and Clostridium, a critical threat to human health. As a novel antibacterial agent against foodborne pathogens, endolysins are peptidoglycan hydrolases encoded by bacteriophages that lyse bacterial cells by targeting their cell wall, notably in Gram-positive bacteria due to their naturally exposed peptidoglycan layer. These lytic enzymes have gained scientists' interest in recent years due to their selectivity, mode of action, engineering potential, and lack of resistance mechanisms. The use of endolysins for food safety has undergone significant improvements, which are summarised and discussed in this review. Endolysins can remove bacterial biofilms of foodborne pathogens and their cell wall-binding domain can be employed as a tool for quick detection of foodborne pathogens. We explained the applications of endolysin for eliminating pathogenic bacteria in livestock and various food matrices, as well as the limitations and challenges in use as a dietary supplement. We also highlight the novel techniques of the development of engineering endolysin for targeting Gram-negative bacterial pathogens. In conclusion, endolysin is safe and effective against foodborne pathogens and has no adverse effect on human cells and beneficial microbiota. As a result, endolysin could be employed as a functional bio-preservative agent to improve food stability and safety and maintain the natural taste of food quality.